2020
DOI: 10.4143/crt.2019.242
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cognitive Impairment in High-Grade Glioma Patients Treated with Postoperative Radiochemotherapy

Abstract: PurposeFractionated radiotherapy as well as concomitant and adjuvant chemotherapy such as temozolomide for postoperative high-grade glioma (HGG) patients improves progression-free survival and overall survival. Multiple factors such as chemotherapy, radiotherapy, tumor grade, residual tumor volume, and genetic modifications might play a role in the formation of cognitive impairment. The risk factors of cognitive impairment in postoperative patients with HGG receiving radiotherapy and chemotherapy remains a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…The majority of patients with grade III or IV gliomas and selected patients with grade II gliomas are scheduled for radiochemotherapy, mainly following neurosurgical resection (4)(5)(6). This situation may produce significant emotional distress for the patients due to fears regarding the treatment procedure, potential side effects, and unsatisfactory treatment outcomes including progression or recurrence of the glioma (7)(8)(9)(10)(17)(18)(19). These fears may lead to sleep problems that can significantly impair the patients' quality of life (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients with grade III or IV gliomas and selected patients with grade II gliomas are scheduled for radiochemotherapy, mainly following neurosurgical resection (4)(5)(6). This situation may produce significant emotional distress for the patients due to fears regarding the treatment procedure, potential side effects, and unsatisfactory treatment outcomes including progression or recurrence of the glioma (7)(8)(9)(10)(17)(18)(19). These fears may lead to sleep problems that can significantly impair the patients' quality of life (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Meyers and Wefel [ 26 ] opined that MMSE as a screening technique of NCF might fail to detect modest cognitive alterations because it lacks the sensitivity to identify frontal-subcortical network disruption, which is frequently associated with radiation therapy in the brain. The Montreal Cognitive Assessment is advocated to be a tool with higher sensitivity and greater comprehensive coverage for detecting even mild decline in NCF and has been used in studies of HGG patients [ 27 28 ]. However, it is dependent on the education levels of patients as it takes into account the years of education received and requires corrections to be made accordingly to eliminate bias.…”
Section: Discussionmentioning
confidence: 99%
“…With the trend of incorporating molecular and genetic markers into the classification and management of gliomas, newer risk factors have emerged which impact the NCF in these patients. In a large prospective analysis of 229 HGG patients receiving adjuvant CRT from China, Wang et al [ 28 ] found that apart from known prognostic factors like GBM histology and residual tumor volume, unmethylated O 6 -methylguanine-DNA methyltransferase (MGMT) promoter status also negatively impacted NCF in an independent manner. MGMT is a DNA repair protein and its unmethylated status in the tumor cells is known to cause resistance to TMZ chemotherapy with poorer survival [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cg18583565 is mapped to genes MGMT , which might be a risk factor for cognitive impairment (50), although the site is located to the gene body. Another probe (cg05065507) is mapped to the gene body of TACSTD2 ; overexpression of TACSTD 2 (also known as TROP2 ) has been reported in multiple cancers (47).…”
Section: Discussionmentioning
confidence: 99%